PENGETAHUAN MENURUT HINDU DAN IMPLIKASINYA TERHADAP PENDIDIKAN MANUSIA SEUTUHNYA - SUKADI SUKADI (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
Appropriate source, according to Hindu knowledge includes knowledge of spiritual, moral knowledge, social knowledge, knowledge of intellectual, physical and sensory knowledge. Fifth human knowledge system was developed as an integrated system. Education according to Hindu, has the obligation to develop a unified system that knowledge to themselves all students, in order to allow it to have intelligence and consciousness double (multiple). Only with the educational process capable of empowering knowledge system as it is, people will be able to grow and develop fully (fully functioning person). It is clear that education in Hindu ideology to support the establishment of a human with multiple intelligences, developed into a fully human, and develop into a human being with the acquisition of knowledge, values ??and attitudes, and skills of both aparawidya (worldly knowledge) and parawidya (noetic knowledge).